SPECIFIC CHARACTERISTICS OF THE PREPARATION OF FUTURE PHYSICAL EDUCATION TEACHERS FOR SPORTS TOURISM (Scientific journal of the Fergana State University, 2023)
This article describes the peculiarities of training future physical education teachers for sports tourism, opinions on the development of various reforms in society.